Process evaluation of a brief messaging intervention to improve diabetes treatment adherence in sub-Saharan Africa - N. Leon; H. Namadingo; S. Cooper; K. Bobrow; C. Mwantisi; M. Nyasulu; N. Sicwebu; A. Crampin; N. Levitt; A. Farmer (BMC, 2021)
Abstract Background The SMS text Adherence suppoRt for people with type 2 diabetes (StAR2D) intervention is a pragmatic randomised controlled trial, testing the effectiveness of brief text messaging for improving clinical outcomes and medication adherence. The intervention did not impact glycaemic control. We conducted a pre-and post-trial process evaluation alongside the StAR2D study in Malawi and South Africa, exploring the experiences and perceptions of patient participants, to better understand potential underlying reasons for the trial outcomes. Methods We employed a qualitative research design, including conducting semi structured in-depth interviews and focus groups at both trial sites. Purposive sampling was used to ensure representation of a wide range of patients with type 2 diabetes with regards to age, gender, ethnicity, language, and duration of diabetes. We interviewed the same participants at baseline and at the end of the trial. We used within-case and across-case thematic analysis to identify key themes. Results Brief messages delivered by text were acceptable and useful for addressing informational and support needs for participants. Some participants reported behaviour changes because of the text reminders and advice on a healthy lifestyle. Both participating in the trial and the messages were experienced as a source of support, caring, and motivation. Participants' ability to act on the messages was limited. A common theme was frustration over the lack of ability to effectively control one's blood glucose level. They reported a range of routinised, partial diabetes care adherence behaviours, shaped by complex and interacting individual, social, and health service factors. Participant responses and intervention impact were similar across sites, despite differences in health services. Conclusion This process evaluation provided context and insight into the factors influencing participants' engagement with the text messaging intervention. The complex context in which patients take their diabetes medication, may explain in part, why brief text messaging may have been insufficient to bring about changes in health outcomes. The scale of need for self-management and health service support, suggests that health system strengthening, and other forms of self-management support should accompany digital communication interventions. (Current Controlled Trials ISRCTN70768808 , registered 03/08/2015.)